Towards circular fashion: management strategies promoting circular behaviour along the value chain - Abdelmeguid, Aya; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Elsevier, 2024)
The fashion industry is a significant driver of cultural, societal, and economic growth worldwide, but its traditional linear approach has led to negative environmental and social impacts. This study addresses the need to transition towards sustainable and circular practices by exploring the relationship between management strategies and behaviours across the fashion value chain. Through 10 semi-structured interviews with top industry decision-makers, thematic analysis revealed eight core themes, including collaborations, marketing strategies, product-related characteristics, education and awareness, business models, integration of technology, regulations and legislation, and strategic planning. The study provides targeted recommendations for stakeholders to promote a more sustainable and circular behaviour in the fashion industry. For instance, it emphasises strategic partnerships with suppliers, waste management companies, and consumers to minimise waste and promote circularity across the value chain. It urges the adoption of sustainable materials and eco-friendly designs for environmentally conscious consumers and encourages visual storytelling for transparency. Additionally, the study highlights the need for circular business models, recommending on-demand and made-to-measure manufacturing to align production with demand and reduce overproduction. Offering end-of-life strategies such as take-back programs, recycling initiatives, and repair services extends product lifecycles and creates sustainable value. Integrating advanced technologies such as digital IDs improves supply chain transparency and accountability. These actionable recommendations guided the development of a comprehensive framework for the practical application of sustainable and circular practices across the value chain, offering industry practitioners, researchers and policymakers effective strategies for driving impactful change within the fashion industry.
Keywords: Circular economy; Sustainability; Fashion; Management strategies; Behaviour; Value chain